Manipulating the electronic configuration of Fe–N4 sites by an electron-withdrawing/donating strategy with improved oxygen electroreduction performance. (6th April 2022) - Wu, Yonggan; Tang, Xiannong; Zhang, Fangjun; Li, Longbin; Zhai, Weijuan; Huang, Bingyu; Hu, Ting; Lützenkirchen-Hecht, Dirk; Yuan, Kai; Chen, Yiwang
Abstract : A facile boron induced electron-withdrawing/donating strategy is demonstrated to regulate the electronic configuration of Fe–N4 sites in Fe–N–C catalysts to optimize the absorption/desorption of oxygen intermediates during the oxygen reduction reaction. Abstract : Fe–N4 sites anchored on carbon (Fe–N–C) materials have drawn increasing interest on account of their remarkable electrocatalytic activity for the oxygen reduction reaction (ORR). Nevertheless, the Fe–N4 sites with a symmetric electronic configuration exhibit too strong binding energy between the Fe center and oxygen intermediates toward the ORR. Herein, we report a facile boron induced electron-withdrawing/donating strategy for manipulating the electronic configuration of Fe–N4 sites, and constructed Fe single-atoms anchored on B and N co-doped carbon (Fe-SA/BNC). Compared to the Fe single-atoms anchored on the N doped carbon (Fe-SA/NC) counterpart, the adjacent boron atoms induce more electrons to accumulate at Fe–N4 sites and optimize the absorption/desorption of oxygen intermediates in Fe-SA/BNC. Besides, Fe-SA/BNC features a large specific surface area, hierarchical porous architecture and low electrochemical impedance, which contribute to fast charge/mass transport. Thus, Fe-SA/BNC displays exceptional ORR activity with a half-wave potential of 0.910 V, surpassing those of Fe-SA/NC (0.889 V) and Pt/C (0.870 V). Furthermore, liquid and flexible solid-state Zn–air batteries equipped with Fe-SA/BNC achieve a high peak power density of 308.3 and 62.9 mW cm −2, respectively. This work not only offers an effective strategy to modify the electronic structure of Fe–N4 sites with improved ORR activity, but also paves the way for preparing high-performance single-atom catalysts.